2019
DOI: 10.4314/rjmhs.v2i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy is family planning: factors affecting uptake among men in eastern province of Rwanda

Abstract: BackgroundVasectomy is the only permanent method of male contraception. It is safer, cheaper, and easier to provide than female sterilisation. Men typically take a vocal role as decision-makers in Africa, yet it is women who take family planning (FP) action. Objective To assess the knowledge and attitude of men toward vasectomy as a method of FP in the Eastern Province of Rwanda. Methods A cross-sectional design, and systematic sampling of every other household was used in a selected area. The sample size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
4
2
1
Order By: Relevance
“…Among Muslim men, only 1.8% underwent male sterilization which was quite low compared to Hindus (3.5%). It was in concordance with a study in Rwanda by Ntakirutimana et al (15) which reported that Catholics [OR:3.7(1.8-4.2)] and Protestants [OR:5.4(4.4-8.5)] are more likely to accept vasectomy compared to Muslim men. Whereas, the study in Borno by Aji et al (17) reported that the attitude of married Muslim men towards family planning is mainly negative because they believe that Islam is against FP.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among Muslim men, only 1.8% underwent male sterilization which was quite low compared to Hindus (3.5%). It was in concordance with a study in Rwanda by Ntakirutimana et al (15) which reported that Catholics [OR:3.7(1.8-4.2)] and Protestants [OR:5.4(4.4-8.5)] are more likely to accept vasectomy compared to Muslim men. Whereas, the study in Borno by Aji et al (17) reported that the attitude of married Muslim men towards family planning is mainly negative because they believe that Islam is against FP.…”
Section: Discussionsupporting
confidence: 92%
“…(12,13,14) Educational level of both the partners plays a crucial role in the decision of male sterilization as reported by a south Indian (10) and other studies around the world. (12,13,14,15,16) We did not find such an association between educational level and male sterilization. This may be because, we have only enrolled those who were using modern methods of family planning in our sample.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The result of this study revealed that as the educational status of the participant increases the knowledge level of vasectomy also increased linearly. This finding is supported by studies conducted in Rwanda, 24 Gondar, 26 and Dangila Town. 27 The reason for this might be that educated men are more likely to be exposed to different media.…”
Section: Discussionsupporting
confidence: 74%
“…Many other studies on vasectomy in West Africa reviewed report that fear, and religious and cultural beliefs, which are also framed as a lack of knowledge, contribute to the poor uptake of vasectomy in the region. [40][41][42][43] . These studies recommend increased publicity and public awareness campaigns on vasectomy.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%